2006
DOI: 10.1063/1.2218463
|View full text |Cite
|
Sign up to set email alerts
|

Low-voltage operation of metal-ferroelectric-insulator-semiconductor diodes incorporating a ferroelectric polyvinylidene fluoride copolymer Langmuir-Blodgett film

Abstract: Kohlstedt, Hermann; Fitsilis, M.; Waser, R.; Reese, T.J.; Ducharme, Stephen; and Rije, E., "Low-voltage operation of metalferroelectric-insulator-semiconductor diodes incorporating a ferroelectric polyvinylidene fluoride copolymer Langmuir-Blodgett film" (2006 We report the electrical characteristics of metal-ferroelectric-insulator-semiconductor structures, where the ferroelectric layer is a Langmuir-Blodgett film of a copolymer of 70% vinylidene fluoride and 30% trifluoroethylene. The 36-nm thick copolymer f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
42
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 22 publications
(16 reference statements)
0
42
0
Order By: Relevance
“…2,17 The contrasting results can be explained by the present use of an organic semiconductor instead of silicon. The latter forms a native oxide layer at the gateinsulator interface which can suppress ferroelectric switching.…”
Section: -4mentioning
confidence: 77%
“…2,17 The contrasting results can be explained by the present use of an organic semiconductor instead of silicon. The latter forms a native oxide layer at the gateinsulator interface which can suppress ferroelectric switching.…”
Section: -4mentioning
confidence: 77%
“…The width of the hysteresis loop is called the memory window and is one of the most important characteristics of an FeFET memory element. The memory window is also evident in measurements of device capacitance C versus gate voltage V g as in an MFIS, 24 as shown in Fig. 3.…”
mentioning
confidence: 90%
“…Once the ferroelectric polarization in the off state falls so that this condition is no longer met, the on and off states of the FeFET are indistinguishable even if the on state is completely stable. Therefore, the capacitance state retention study that was previously reported 24 is better suited for a discussion of the dominant mechanisms for state relaxation. Since the capacitance hysteresis ͑Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations